An analysis of the financial liquidity management strategy in construction companies operating in the Podkarpackie Province - Grzegorz Zimon; Joanna Nakonieczny; Katarzyna Chudy-Laskowska; Magdalena Wójcik-Jurkiewicz; Konrad Kochański (Risks, 2021)
The activity of each construction company in conditions of high competitiveness is exposed to a number of risks that make it difficult to maintain high financial liquidity. In order to provide the continuity of ongoing economic processes and to be able to develop, entities are forced to build optimal financial management strategies for them. Enterprises can choose between a conservative, moderate and aggressive strategy, which is largely determined by the way they manage their current assets and short-term liabilities. In the case of construction companies, it is also not without significance that they are particularly sensitive to fluctuations in the economic situation and changes in the macroeconomic environment, which imply the availability of funds. The purpose of this paper is to analyze the financial liquidity management strategy of construction sector Polish enterprises from the Podkarpackie Province in 2017-2019 and the impact of this strategy on the profitability of the surveyed entities. In order to achieve the goal, the issues related to the classification of financial liquidity and individual liquidity management strategies are discussed. The issues and the goal set determined the choice of research methods. Literature studies, the Mann-Whitney U test, cluster analysis and Ward's method were used. The research was carried out on a group of the 10 largest construction companies from the Podkarpackie Province. The selection of entities for the research was deliberately based on enterprises that submit their financial statements to the National Court Register. The conducted research showed that small and large enterprises applied different liquidity management policies even though they operate in the same industry and region. The small entities preferred a conservative strategy, while large entities preferred a moderate strategy. The existence of an inverse relationship between the phenomenon of financial liquidity and profitability of economic entities was also confirmed.
Keywords: 330; financial liquidity; risks; SMEs; profitability; construction sector